ANALISIS KETIDAKEFEKTIFAN DEKLARASI PANMUNJOM SEBAGAI UPAYA REUNIFIKASI SEMENANJUNG KOREA - Nabila Lam'anah (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
North and South Korea have made various peace efforts to overcome the issue of denuclearization of the Korean Peninsula. However, so far the peace efforts that have been made by the two Koreas have not been successful. This is caused by the relations between the two countries which are still marked by mutual distrust, lack of cooperation, hatred, and ideological conflict. Then, the two Koreas made peace efforts again called the Panmunjom Declaration in 2018. The main points of this declaration are a commitment to end the confrontation of the legacy of war that has been going on for a long time, to increase cooperative relations between the Koreas, and denuclearize the Korean Peninsula region. At first, the Panmunjom Declaration became a new achievement in the peace of the Korean Peninsula. Over time, the Panmunjom Declaration became ineffective in carrying out its role as a medium for creating peace and denuclearizing the region. This research will answer the question